Implementing Smart Statistics Toolkit in the Official Statistics - Osaulenko О. H.; Horobets О. О. (Statistics of Ukraine, 2023)
Important issues of Smart statistics are addressed. The Smart statistics toolkit is analyzed: big data, data of artificial intellect and Internet of things, social media, and administrative data. The study involves conceptualization of the Smart statistics and identification of advantages and threats for the official statistics in using Smart statistics data. A set of principles for operating big data are proposed, with categorizing the sources of big data generation (in conformity with the economic activities), presently demanded by the official statistics and the society (agriculture, health protection, mining industry, mechanical engineering, education, power industry). A smart data system in smart cities is developed, containing the following components: smart house, smart environment, smart control, smart traffic, smart health, and smart citizen. It is determined that the system’s objective is to create the smart environment and simplify the way of life through saving time, energy and money. The components of personalized collection and dissemination of data are determined. The artificial intelligence (AI) is considered as a component of the Smart statistics conception. In this article’s context, the authors observe that using AI causes ethical discourses on issues such as property right for data, transparence and accountability of data. These discourses need to accounted for, in order to assure that AI technologies are used by the official statistics in a responsible and ethical manner. Based on the results of the study, it is concluded that now it is necessary to create logical and adequate approaches to elaborating a methodology for collection, processing, grouping and analysis of statistical data from alternative information sources. It is argued that in spite of the advantages of the smart statistics toolkit and potentially positive results of its implementation in the official statistics, present-day Ukraine is not ready to face the threats involved in it given the war conditions and lack of a regulatory framework for its use. Further studies on this theme have to focus on in-depth analysis of Smart statistics and search for optimal ways for implementing its toolkit in the official statistics of Ukraine.